SPE Improved Oil Recovery Conference 2016
DOI: 10.2118/179559-ms
|View full text |Cite
|
Sign up to set email alerts
|

Low Tension Gas Flooding as a Novel EOR Method: An Experimental and Theoretical Investigation

Abstract: Low Tension Gas (LTG) flooding is a novel EOR process which can address challenging reservoir conditions such as high salinity, high temperature, and tight rock. Current process understanding is limited, and a joint experimental and modeling approach allows for both interpretation and insight into the complex interactions between the key process parameters of salinity gradient, foam strength, microemulsion phase behavior, and phase desaturation in order to achieve a physically correct and predictive process mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…low permeability regions (Shupe 1981). Variants of the ASF process were investigated by others in literature (Srivastava et al 2009;Szlendak et al 2013;Tang et al 2014;Jong et al 2016) but they did not provide clues about oil mobilisation and displacement mechanisms.…”
mentioning
confidence: 99%
“…low permeability regions (Shupe 1981). Variants of the ASF process were investigated by others in literature (Srivastava et al 2009;Szlendak et al 2013;Tang et al 2014;Jong et al 2016) but they did not provide clues about oil mobilisation and displacement mechanisms.…”
mentioning
confidence: 99%
“…The only difference between Corefloods 2 and 1 was that the slug injection salinity in Coreflood 2 was at the boundary between Type I and Type III (130,000 ppm), unlike the optimum Type III salinity (148,000 ppm) in Coreflood 1. Jong et al (2016) experimentally observed that injection at sub-optimum salinity is better for oil recovery in higher-permeability rocks. These experiments were done in sandstone rocks at low formation and injection salinity.…”
Section: Effect Of Slug Injection Salinity (Coreflood 2)mentioning
confidence: 98%
“…Compared to coreflood 1 (Figure 2), the pressure drop curves show sharp increases and decreases in successive sections, indicating better propagation of the oil bank. It has been experimentally observed that injection at sub-optimum salinity is better for oil recovery in higher permeability rocks, while injection at optimum salinity is beneficial for oil recovery in tight rocks (Jong and Nguyen, 2016). Even though the oil breaks through earlier, it is observed that the oil cut curve is elongated and does not show a sharp increase.…”
Section: Surfactant Formulation and Salinity Effectmentioning
confidence: 99%